Thrombolysis in Newborns and Infants - Nowak-Göttl, U.; Auberger, K.; Halimeh, S.; Junker, R.; Klinge, J.; Kreuz, W. D.; Ries, M.; Schlegel, N. (Thrombosis and Haemostasis, 1999)
This review analyses literature reports from 1970 to 1998 assessing the use of streptokinase (SK), urokinase (UK) or recombinant tissuetype plasminogen activator (rt-PA) for thrombolytic therapy in neonates and infants. From 1970 to 1998 182 infants were reported to have received SK (n = 54; 29.5%), UK (n = 41; 22.5%) or rt-PA (n = 87; 48%). During thrombolytic therapy no concomitant heparin administration or low dose heparin therapy (5 U/kg/h) were recorded. To perform reocclusion prophylactics heparin was reinitiated at the end of thrombolytic therapy usually in the recommended dosage of 20 U/kg/h. The overall thrombolytic patency rate in neonates varied from 39% to 86%. Besides bleeding from local puncture sites or recent catheterisation sites (10.4%), pulmonary embolism was reported in 1.1% of the 182 infants. Major bleeding complications, i.e. pulmonary bleeding (0.6%), gastrointestinal bleeding (0.6%) or intraventricular haemorrhage (IVH 2.7%) are rarely reported side effects and only 2 thrombolysis related deaths due to haemorrhage were mentioned. Bleedings reported in the central nervous system (n = 4) mainly occurred in preterm infants (n = 3). In conclusion, data of this preliminary analysis suggest that there is no big difference (p = 0.09; χ2-test) in the efficacy rate between the 3 thrombolytic agents used in the first year of life. In each case an assessment must be made with respect to the relative benefit conferred by thrombolytic therapy in preventing organ or limb damage versus the potential side effects, costs and inconvenience for the childhood patient. Controlled prospective multicentre studies on thrombolytic therapy in neonates and infants are recommended to evaluate patency rates and adverse effects for the different thrombolytic agents used.
Keywords: Thrombolysis; heparin; infancy; intracranial haemorrhage